Migration and the globalisation of health care :The health worker exodus? - Connell, John (Edward Elgar, 2010)
The international migration of health workers, described by Nelson Mandela as the 'poaching' of desperately needed skills from under-privileged regions, has a controversial recent history. This text examines skilled migration, & the economic, social & cultural rationale behind the rise of complex & now global markets.